181k views
5 votes
Determine f(-2/3) for the function f(x)=3x²+2x+1​

User Mcgtrt
by
5.1k points

2 Answers

2 votes

Answer:

1

Explanation:

To evaluate, substitute x = -
(2)/(3) into f(x), that is

f(-
(2)/(3) )

= 3(-
(2)/(3) )² + 2(-
(2)/(3) ) + 1

= 3(
(4)/(9) ) -
(4)/(3) + 1

=
(4)/(3) -
(4)/(3) + 1

= 0 + 1

= 1

User MohamedSanaulla
by
6.1k points
4 votes

Answer:

1

Explanation:

f(x) = 3x² + 2x + 1

f(-2/3) = 3x² + 2x +1

f(-2/3) = 3(-2/3)² + 2(-2/3) + 1

Substitute the value in for all the x's

f(-2/3) = 3(4/9) + 2(-2/3) + 1

f(-2/3) = 12/9 + (-4/3) + 1

f(-2/3) = 4/3 + (-4/3) + 1

Subtracting 4/3 by (-4/3) gets you 0 so I didn't write it down.

f(-2/3) = 1

So, the answer I got is 1

User Rytis Alekna
by
5.3k points